Ukrainian Anthropology: a Glimpse from the Past - Vitalii Kononenko (Vasyl Stefanyk Precarpathian National University, 2022)
Review - Vovk, Kh. (1976). Studies in Ukrainian ethnography and anthropology. New York: Goverlia. 356 p.